A inexecução temporária de obrigações contratuais: o tratamento no direito brasileiro e uma perspectiva sob a ótica do common law - Thiago Porto Ribeiro (2023)
The present work aimed to analyze the treatment in Brazilian law for situations of temporary non-performance of obligations, as well as to evaluate the perspective of common law on the subject. As is known, the contract formalizes in present terms situations that will be faced in an uncertain future. Originally, the idea of absolute liability of the contracting parties was present, notwithstanding any future adverse situation not foreseen at the time of the execution of the agreement. However, in search of equity, the idea of resumption of the state of subsistence of things for the maintenance of contractual balance developed over time. In Brazil, it is observed that there is no organized system to deal with disturbance situations in performance, and the rules which are provided only relates to the possibility of contractual resolution in cases of excessive burden and contractual revision for pecuniary obligations to seek recovery of the real value of the obligation. Situations of temporary impossibility are treated in a scattered way and in specific chapters. Moreover, there is no solution or general rule that allows the suspension of performance and the consequent maintenance of the contract. A look at the perspective of common law, notably concerning the doctrine of frustration, enriches the debate and allows for a more objective approach that respects private autonomy. The relevance of the subject is therefore justified by the observation of the absence of organized rules in our legal system and the need for a proposal, whether contractual, legal or hermeneutic, to deal with a subject that represents discomfort for contractors facing crisis situations.